Origin of the IRAS Vela Shell: New Insights from 3D Dust Mapping - Bore Annie Gao; Catherine Zucker; Tirupati Kumara Sridharan; Cameren Swiggum; Shmuel Bialy; Theo J. O’Neill; J. E. G. Peek; Luciana Bianchi; Robert Benjamin; Lewis McCallum; Alyssa Goodman; João Alves; et al. (The Astrophysical Journal)
The IRAS Vela Shell (IVS) is a structure of enhanced far-IR (FIR) emission located toward the Gum Nebula, a prominent region of H α emission in the local Milky Way shaped by various galactic stellar feedback over the past several million years. We constrain the 3D spatial geometry of the IVS using a parsec-resolution 3D dust map and contextualize it within the broader Gum Nebula. Our analysis reveals a dense, bowl-like IVS structure below the Galactic plane, with a more diffuse component above. We obtain a total shell mass of $5.{1}_{-2.4}^{+2.4}× 1{0}^{4}\,M_{\odot }$ and, incorporating previous studies on shell expansion, a momentum of $6.{0}_{-3.4}^{+4.7}× 1{0}^{5}\,M_{\odot }\,{\rm{km}}\,{{\rm{s}}}^{-1}$ . We find a spatial correlation between the morphology of the dust-traced IVS and the Gum Nebula’s H α emission when projected onto the sky. We quantify contributions of feedback from stellar winds, an expanding H ii region, and supernovae to the IVS formation, finding that stellar winds are subdominant. Our momentum analysis shows that both an H ii region and supernova feedback could drive the shell’s expansion. Using astrometric constraints from Gaia and Hipparcos, we trace back nearby feedback sources and find that the massive stars γ 2 Velorum and ζ Puppis are currently within the IVS, producing enough ionizing luminosity to form an H ii region of comparable size. Alternatively, if the IVS’ momentum is primarily driven by supernovae, one to two events would be required. We also identify several young massive clusters that could have hosted supernovae within the past 3 Myr.